The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1073/pnas.2006024117
|View full text |Cite
|
Sign up to set email alerts
|

Diel variability of methane emissions from lakes

Abstract: Lakes are considered the second largest natural source of atmospheric methane (CH4). However, current estimates are still uncertain and do not account for diel variability of CH4 emissions. In this study, we performed high-resolution measurements of CH4 flux from several lakes, using an automated and sensor-based flux measurement approach (in total 4,580 measurements), and demonstrated a clear and consistent diel lake CH4 flux pattern during stratification and mixing periods. The maximum of CH4 flux were alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 54 publications
7
74
5
Order By: Relevance
“…Lakes showed concentrations similar to those of Pavel et al (2009) (see Table A1), although taken roughly 10 years later. The comparison to this earlier study indicates carbon turnover had not significantly changed during this period (Tudor et al, 2016;Spiridon et al, 2018). These concentrations ranged from the lowest 0.113 µmol L −1 to the highest 11.3 µmol L −1 both in May (largest concentration close to a channel).…”
Section: Ch 4 Dynamics In Lakessupporting
confidence: 47%
See 2 more Smart Citations
“…Lakes showed concentrations similar to those of Pavel et al (2009) (see Table A1), although taken roughly 10 years later. The comparison to this earlier study indicates carbon turnover had not significantly changed during this period (Tudor et al, 2016;Spiridon et al, 2018). These concentrations ranged from the lowest 0.113 µmol L −1 to the highest 11.3 µmol L −1 both in May (largest concentration close to a channel).…”
Section: Ch 4 Dynamics In Lakessupporting
confidence: 47%
“…Since the 1970s, the Danube Delta has been subject to eutrophication, with its peak during 1987-1988 (Cristofor et al, 1993;Galatchi and Tudor, 2006;Enache et al, 2019). After a decrease in nutrient loads in the 1990s, due to socioeconomic changes in eastern Europe, a slow decline of nutrient levels was observed (Rîşnoveanu et al, 2004;Pavel et al, 2009); however, more recent levels comparable to those in 1988 were reported (Tudor et al, 2016;Spiridon et al, 2018).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The availability of automated sensors capable of high-frequency measurements and long-term deployments make such an ideal framework realizable. The present study focused on CO 2 , but methane (CH 4 ) is an even more potent greenhouse gas (35) which also accumulates in the hypolimnia of lakes and then can be emitted to the atmosphere (8,36,37), and its emission from the reservoir surface can vary daily (38). Future research into the carbon cycling of dams and the emission hotspots downstream should therefore also assess methane fluxes in the downstream river system and their seasonal and subdaily variation.…”
Section: A a A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A A Amentioning
confidence: 99%
“…10.1029/2020JG006014 8 of 19 followed by averaging the two annual estimates into an annual average estimate for each gas. Given that our calculations of total diffusive C emission are only based on daytime measurements (between 9 and 18 h), our results may be biased since they do not include any potential diel variations in diffusive C emissions and any specific mixing dynamics happening in the water column during the entire period of each hydrological season represented here (Podgrajsek et al, 2014;Rõõm et al, 2014;Sieczko et al, 2020).…”
Section: Discussionmentioning
confidence: 99%